An Efficient Ciphertext Retrieval Scheme Based on Homomorphic Encryption for Multiple Data Owners in Hybrid Cloud - Heng He; Renju Chen; Chengyu Liu; Ke Feng; Xiaohu Zhou (IEEE Access, 2021)
More and more individuals and enterprises outsource data and applications to cloud servers in recent years. Since the public cloud servers are not completely trusted, users usually encrypt important data before sending it to cloud servers. As a result, ciphertext retrieval technology has gradually become a research hotspot. In the existing related schemes, there are some defects such as not supporting “multiple owners” mode and multi-keyword retrieval, having low retrieval efficiency, accuracy and security, and difficult data updating. Hence, we propose an efficient Ciphertext Retrieval scheme based on Homomorphic encryption for Multiple data owners in hybrid cloud (CRHM), in which the public cloud server and the private cloud server cooperate to perform the ciphertext retrieval. In CRHM, an encrypted balanced binary index tree structure and a homomorphic encryption method based on large integer operations are designed to support “multiple owners” mode and multi-keyword ranked retrieval. The security analysis shows that CRHM can effectively guarantee the privacy and security of user file and retrieval, and the performance evaluation demonstrates that compared with the existing related schemes, CRHM has high efficiency in the index generation and retrieval processes, while keeps relatively high retrieval accuracy.